Chronic Physical Activity for Attention Deficit Hyperactivity Disorder and/or Autism Spectrum Disorder in Children: A Meta-Analysis of Randomized Controlled Trials - Zhang, Meiqi; Liu, Zhan; Ma, Hongtao; Smith, Daniel M. (Frontiers in Behavioral Neuroscience, 2020)
Purpose: To explore the effects of physical activity (PA) intervention on executive function (EF) and motor skills (MS) among children with attention deficit hyperactivity disorder 1 and/or autism spectrum disorder (ASD). Methods: Relevant studies were sourced from PubMed, Web of Science, EMBASE, Cochrane Library, CNKI, and Wanfang Data. Only randomized controlled trials (RCT) were included based upon the following criteria: (1) participants were children and clinically diagnosed with ADHD/ASD, (2) EF (e.g., cognitive flexibility) and/or MS (e.g., gross motor skills) were measured at baseline and post-intervention and compared with an eligible control group. Results: Twelve studies involving 394 participants were finally identified. PA elicited significant improvements in EF and MS in children with ADHD/ASD. Regarding changes in the EF of participants, PA showed a great improvement in overall EF (standardized mean difference (SMD) : 0.75 , 95% confidence interval [CI] 0.41 to 1.09, p < 0.00001), inhibitory control (SMD: 1.13, 95% CI 0.49 to 1.76, p<0.00001) and cognitive flexibility (SMD: 0.58, 95% CI 0.07 to1.09, p = 0.02), but no improvement in working memory. Similar results were also found with respect to gross motor skills (SMD: 0.89, 95% CI 0.44 to 1.35, p = 0.18), but no significant changes were found in fine motor skills. Conclusion: PA may promote EF and MS in children with ADHD/ASD, especially in inhibitory control, cognitive flexibility, and gross motor skills. PROSPERO registration number: CRD42019118622